The dimensions of reflective practice: a teacher educator's and nurse educator's perspective. Issue 3 (3rd May 2020) - Lubbe, Welma; Botha, Carolina Stephanusina
ABSTRACT: This article aims to accentuate the value of reflective practices in the lived experiences and professional development of a teacher educator and a nursing educator at a higher education institution in South Africa. Reflective practice promotes the continuous (re)creation of local knowledge through a critical reflection on beliefs, assumptions, experiences and practices in order to identify successful strategies for teaching practice, reflect upon challenges, adapt, and evolve their practice. Reflective practice encapsulates a process of continuous learning and growth that not only resonates with pedagogical and methodological viewpoints and also ontological and epistemological situatedness and is at the same time aligned with national and institutional aims and requirements. In this self-study project based on LaBoskey's five characteristics of self-study, educators in higher education become both the researcher and the researched and the emphasis of the research is on the self as a theorist, researcher and practitioner. The authors explore and elucidate their journey of discovery towards the various dimensions of their reflective practice through a critical evaluation of their teaching and learning theory and of their teaching and assessment strategies. Both authors have been awarded institutional teaching excellence awards. This article contributes to their joint discourse on higher education as well as their conceptualization of their respective scholarships of teaching and learning.